Lung Perfusion Scanning in Hepatic Cirrhosis - Stanley, N. N. (1972)
Abnormal lung perfusion scans using radioactive particles were found in five out of six cases of hepatic cirrhosis with arterial hypoxaemia. None had clinical evidence of cardiopulmonary disease or signs of pulmonary embolism on arteriography. The scan defects are probably caused by a disorder of the pulmonary microvasculature, which may show regional variation in severity.